2017
DOI: 10.1158/1078-0432.ccr-16-2392
|View full text |Cite
|
Sign up to set email alerts
|

Bioluminescence Imaging Enhances Analysis of Drug Responses in a Patient-Derived Xenograft Model of Pediatric ALL

Abstract: Purpose Robust preclinical models of pediatric acute lymphoblastic leukemia (ALL) are essential in prioritizing promising therapies for clinical assessment in high-risk patients. Patient-derived xenograft (PDX) models of ALL provide a clinically relevant platform for assessing novel drugs, with efficacy generally assessed by enumerating circulating human lymphoblasts in mouse peripheral blood (PB) as an indicator of disease burden. While allowing indirect measurement of disease burden in real-time, this techni… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 55 publications
2
15
0
1
Order By: Relevance
“…Assessment of denintuzumab mafodotin activity against ALL‐11 was also monitored by BLI, as this PDX has been lentivirally transduced to stably express firefly luciferase . Imaging data showed a profound decrease in whole animal bioluminescence during the treatment period, with burden continuing to decrease up to 2 weeks following administration of the final dose, suggesting persistence of denintuzumab mafodotin in multiple tissue niches (Figure A and B; Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Assessment of denintuzumab mafodotin activity against ALL‐11 was also monitored by BLI, as this PDX has been lentivirally transduced to stably express firefly luciferase . Imaging data showed a profound decrease in whole animal bioluminescence during the treatment period, with burden continuing to decrease up to 2 weeks following administration of the final dose, suggesting persistence of denintuzumab mafodotin in multiple tissue niches (Figure A and B; Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…Briefly, leukemia cells were inoculated intravenously into groups of eight 6‐ to 8‐week‐old NOD/SCID or NSG mice (Australian BioResources, Moss Vale, NSW, Australia) and leukemia burden monitored via enumeration of human CD45 + (%huCD45 + ) cells versus total CD45 + leukocytes (human plus mouse) in the peripheral blood (PB) and tissues, as outlined previously . Monitoring of leukemia burden using bioluminescence imaging (BLI) was performed as described elsewhere . Previous power calculations indicated that a group size of eight mice was sufficient to detect a twofold difference between control and treated groups at a power of 0.9 and significance of 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations